2016
DOI: 10.1111/jdv.13593
|View full text |Cite
|
Sign up to set email alerts
|

Laser therapies for onychomycosis – critical evaluation of methods and effectiveness

Abstract: The number of medical devices designed specifically to treat onychomycosis has recently increased, although their mechanism of action is not clear. We evaluated available laser therapies for onychomycosis by reviewing the existing literature. Twenty-two reports, published in peer-reviewed journals and as white papers out of 926 initial search results conveyed enough details to be included in this study. In most cases, the methodology of the trials described in the papers we reviewed was not comprehensive and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 32 publications
(39 reference statements)
0
25
0
1
Order By: Relevance
“…A substantial difference in mycological cure (culture and microscopy) was found when multiple nails per patient (60%) were used as opposed to one nail per patient (25%), suggesting that a possible overestimation of the antifungal abilities of lasers can occur. Perhaps, the use of the onychomycosis severity index (OSI) could be of assistance in future laser studies . The OSI is a classification system based on nail involvement, how distant the infection is from the matrix, presence of longitudinal streaks and/or thickening of the nail (greater than 2 mm) …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A substantial difference in mycological cure (culture and microscopy) was found when multiple nails per patient (60%) were used as opposed to one nail per patient (25%), suggesting that a possible overestimation of the antifungal abilities of lasers can occur. Perhaps, the use of the onychomycosis severity index (OSI) could be of assistance in future laser studies . The OSI is a classification system based on nail involvement, how distant the infection is from the matrix, presence of longitudinal streaks and/or thickening of the nail (greater than 2 mm) …”
Section: Discussionmentioning
confidence: 99%
“…short vs long‐pulsed, laser model) were not controlled in this review, applicability of this review is limited. Laser parameters can influence the amount of energy delivered to the fungal cells, altering their performance . Laser models such as the Nd:YAG elicit fungicidal effects by creating an accumulation of heat (43–51⁰C) in fungal mycelium .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Nd:YAG lasers were the first medical devices designed specifically for the treatment of onychomycosis, but the outcomes are still contradictory. 53 In one study, a temporary improvement in the appearance of the target nail was observed in 78% of patients and the affected area of the nail plate was reduced by at least 50% from the baseline in 46% of patients, 54 but another group found the 1064nm Nd:YAG laser was not an effective treatment for onychomycosis. 55 In two clinical trials .…”
Section: Accepted Manuscriptmentioning
confidence: 96%